RANCANGAN DAN PEMBUATAN ALAT SIMULASI SISTEM VENTILASI TAMBANG PADA LABORATORIUM UNTUK PEMBELAJARAN VENTILASI TAMBANG - Bambang Heriyadi (Sekolah Tinggi Teknologi Industri Padang, 2017)
Underground mine activities is not detached by mechanical ventilation system for supplying air demand for worker’s breathing, dirty air and toxic gases removing, dust reducing, and heat and humidity controlling. There for makes safer and enjoyable in working. To facility the study of mine ventilation in campus, the simulation study about mechanical underground mine ventilation system was applied. To do this research, the describtion about mechanical ventilation system of underground mine is necersary and also we need pay attention with the parameters in air qualities and quantities controlling witch are not over limit to the limit value (NAB). Describing how to control the air qualities and quantities, the writer got sample as well as PT. AICJ. PT.AICJ’s ventilation system is forcing system with some parameter like air velocity, wet and dry temperature, relative humidity, tunnel dimension, and around of gases concentration in air at mine front. Gases measured to wards the concentration of O2, CO2, CH4, and H2S. In this research, the writer designed and created a simulation of ventilation system, with autoCAD 2014 modeling advises. In the other hand the material that, used for equipment is iron plate 1 mm thickness. Volumetric air flow rate produced by forcing fan (18” diameter size) is 0.23m3/second with 260C effectively temperature. Medium air flow rate is 0.24m/second with is 25,30C effectively temperature. High air flow rate is 0,26m/second with 24,70C effectively temperature, while volumetric air flow rate of forcing fan 16” diameter size is o,26 m3/second with 24,40C effectively temperature, for exhaust fan (4”size) produced 0,18 m3/second volumetric air flow rate with 26,50C effectively temperature . so the simulation equipment ventilation can show measure result by quantity and quality airflow characteristic. Keywords: Ventilation Simulation Equipment, Air Quality, Air Quantity, Ventilation Pressure